Histomorphometric analysis of the endometrium in an ectopic model of endometriosis in mice - Silva, Felipe Rosendo da; Thimoteo, Daniel Soares; Carbonel, Adriana Ferraz; Portugal Fuchs, Luiz Fernando; Sasso, Gisela Rodrigues da Silva; Simoes, Ricardo dos Santos; Invitti, Adriana; Vieira, Renata Ramos; Ferreira, Luiz Philipe de Souza; Silva, Rafael Andre da [UNESP]; Lima, Patricia Daniele Azevedo; Soares Junior, Jose Maria; et al. (Taylor & Francis Ltd, 2022)
Objective: Evaluate histomorphometry of ectopic and eutopic endometrial tissues in receptor mice. Method: Eighteen female Balb/c were divided into 3 groups, 6 animals each: GI Control, no procedure; GII - Sham, animals that had the same procedures as GIII without receiving the ectopic endometrial implant. Instead, they received saline solution; GIII - endometriosis model, animals had surgical intervention with an ectopic endometrial implant. GI and GIII mice were treated with 17 beta-estradiol, 100 mu g/kg each. All animals were euthanized to collect uterine horns, which were fixed in 4% paraformaldehyde, embedded in paraffin, stained with Hematoxilin and Eosin and submitted to histomorphometric analyzes. Data underwent one-way ANOVA followed by Tukey's test. Results: Local tissue growth, showing important lesions and adhesions, as well as dark cysts were noticed. In GIII group, there was an increase in number of blood vessels and glands (GIII >= GI and GIII p > .001). Thickening of the GIII endometrial epithelial was also evident (GIII >= GI and GIII. p > .001). We also noticed an increase in the number of eosinophils (GIII (GIII >= GI and GIII. p > .001). Conclusion: Easy to perform model, capable of reproducing morphological endometriosis characteristics. From our findings, there was an increase of endometrial thickness as well as an increase in the eosinophils population.
Keywords: Mouse; Histomorphometry; Female infertility